The Role of Social Media for Patients and Consumer Health - Lau, A. Y. S.; Siek, K. A.; Fernandez-Luque, L.; Tange, H.; Chhanabhai, P.; Li, S. Y. W.; Elkin, P. L.; Arjabi, A.; Walczowski, L.; Ang, C. S.; Eysenbach, G. (Yearbook of Medical Informatics, 2011)
To provide an overview on social media for consumers and patients in areas of health behaviours and outcomes.A directed review of recent literature.We discuss the limitations and challenges of social media, ranging from social network sites (SNSs), computer games, mobile applications, to online videos. An overview of current users of social media (Generation Y), and potential users (such as low socioeconomic status and the chronically ill populations) is also presented. Future directions in social media research are also discussed.We encouragethe health informaticscommunity to consider the socioeconomic class, age, culture, and literacy level of their populations, and select an appropriate medium and platform when designing social networkedinterventionsforhealth.Little isknown about the impact of second-hand experiences faciliated by social media, nor the quality and safety of social networks on health. Methodologies and theories from human computer interaction, human factors engineering and psychology may help guide the challenges in design-ingand evaluatingsocial networkedinterventionsforhealth. Further, by analysing how people search and navigate social media for health purposes, infodemiology and infoveillance are promising areas of research that should provide valuable insights on present and emergening health behaviours on a population scale.
Keywords: Social media; healthcare consumers; patients; health behaviour; social network